2007
DOI: 10.1080/08982110701630461
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Vaccines: An Illustration of Using PAT Tools for Controlling the Cultivation ofBordetella pertussis

Abstract: An illustration of the operational consistency of the upstream part of a biopharmaceutical process is given. For this purpose four batch cultivations of Bordetella pertussis have been executed under identical conditions. The batches have been monitored by means of two fundamentally different process sensors. First, common single channel measurements such as temperature, pH, dissolved oxygen (DO), and flow rates are used and second, the multichannel measurements from the NIR (Near Infrared) analyzer. Because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Implementation of typical PAT (FDA 2004) sensors such as NIRS during batch fermentation, would generate a continuous, multivariate process fingerprint of the inoculation-to-harvest trajectory. On-line monitoring of nutrient concentrations for automated detection of the harvest point is also possible (Arnold et al, 2002;Ferreira et al, 2005;van Sprang et al, 2007). Such a science-based PAT approach, in combination with the presented model to measure product quality, could result in a process that yields whole-cell vaccines of such intrinsic quality and consistency (Gnoth et al, 2007) that it would change the perspective for the use of the Kendrick potency test (Irwin and Standfast, 1957;Kendrick et al, 1947).…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of typical PAT (FDA 2004) sensors such as NIRS during batch fermentation, would generate a continuous, multivariate process fingerprint of the inoculation-to-harvest trajectory. On-line monitoring of nutrient concentrations for automated detection of the harvest point is also possible (Arnold et al, 2002;Ferreira et al, 2005;van Sprang et al, 2007). Such a science-based PAT approach, in combination with the presented model to measure product quality, could result in a process that yields whole-cell vaccines of such intrinsic quality and consistency (Gnoth et al, 2007) that it would change the perspective for the use of the Kendrick potency test (Irwin and Standfast, 1957;Kendrick et al, 1947).…”
Section: Discussionmentioning
confidence: 99%
“…Setting (b) contains the online measured data of pH, temperature, percentage of DO, and a selection of wavelength of the spectra (1,111–1,397 and 1,587–1,852 nm). This wavelength selection originates from van Sprang et al7 was applied in Soons et al4 and is chosen in this study because the excluded wavelengths correspond to saturated intensities due to water. Both settings, (a) and (b), are augmented by the initial component concentration values of every batch to compare the PLS model to the hybrid model providing the exact same data.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate regression, (nonlinear) partial least square (NPLS), evolving factor analysis, support vector machines, or principal component analysis (PCA) are probably the ones that are most commonly applied and most successful 6, 7. These methods are data driven, and in most cases, they are applied on their own disregarding other valuable process knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…55 The measurements were used for a consistency analysis of the batch process, providing better process understanding which includes the understanding of the variations in the data. MSPC analysis of four batches of data was performed to monitor the batch trajectories, and indicated that one batch had a deviation in the pH.…”
Section: Continuous P Rocess V Alidationmentioning
confidence: 99%